Redesigning care to meet national recommendation of four or more yearly clinic visits in patients with cystic fibrosis. (7th March 2014) - Berlinski, A; Chambers, M J; Willis, L; Homa, K; Com, G
Abstract : Cystic fibrosis (CF) is a chronic disease requiring patients to have frequent specialty healthcare visits to delay progression of lung disease, prevent and treat failure to thrive and initiate early interventions to prevent acute illness and complications. The CF Foundation recommends that patients have visits with the CF care team at least every 3 months. During participation in the CF Foundation Learning and Leadership Collaborative IV, the CF team at Arkansas Children's Hospital initiated quality improvement work with the aim to increase the percentage of patients attending clinic four or more times a year from 35% in 2004 and 56% in 2005 (CF Foundation Registry data) to 90% or greater. We redesigned our scheduling system, rescheduled missed patient appointments in a timely fashion and created a process to monitor attendance. This quality improvement work led to a sustained increase in the percentage of patients attending clinic visits four or more times a year reaching our goal of 90% in 2012. Improvements were also noted in the number of patients with body mass index/weight-for-length centile of 25 or greater, which could be related to more frequent clinic attendance.